Effects of Aminoethoxyvinylglycine on Harvest Time and Fruit Quality of ‘Monroe’ Peaches - Melike Çetinbaş (Journal of Agricultural Sciences)
This study was conducted to prolong the harvest date and enhance the fruit quality of ‘Monroe’ peaches. For this purpose, ReTain containing 15% aminoethoxyvinylglycine (AVG) was applied to the peach fruits. AVG at concentrations of 0, 100, 150 and 200 mg l -1 was sprayed on the peaches 7, 21 and 30 days before commercial harvest. Some fruit quality parameters [fruit weight (g), fruit flesh firmness (N), soluble solids content (SSC, %), titratable acidity (TA, %), fruit colour (L*, a*, b*), sugar content, delay in harvest, ethylene production (µl kg-1 h-1) and respiration rate (ml CO2 kg-1 h-1)] were measured for each treatment. Fruit maturity was delayed about 4-6 days more in AVG-applied fruits than in the control group. A sequential harvest was completed 6-7 days before the normal harvest time. Application of AVG increased the fruit size and fruit weight of ‘Monroe’ peach. AVGsprayed fruits were firmer than the fruits of control group. AVG applications also decreased ethylene production and the respiration rate of fruits. As a results, application AVG of 100 or 200 mg l -1 concentrations 30 days before commercial harvest for 'Monroe' peach varieties can be recommended.